Pengembangan E-Modul PPK EM_PROSOL Berbasis Siri’ Na Pacce dalam Upaya Menumbuhkan Empati dan Perilaku Prososial Siswa - Nurkiama, Rezki; Sinring, Abdullah; Harum, Akhmad (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
This study focuses on developing an E-Module for Strengthening Siri'na Pacce Based Character Education in an Effort to Cultivate Empathy and Prosocial Behavior Students. This research aims to achieve: First, obtain an overview of e-module needs analysis. Second, creating an E-Module Development Prototype to strengthen character education based on siri' na pacce to foster empathy and prosocial behavior in the target group. Third, determine the validity and practicality of the e-module. Using a research and development (R&D) approach with the ADDIE model, this research uses questionnaires, interviews and documentation as research instruments, applying quantitative descriptive analysis techniques and qualitative content analysis. The findings show the following: Firstly, the use of attractive media is very much needed in the service delivery process, confirming the need for the presence of E-Modules in the service delivery process. Second, the e-module prototype includes three topics, each of which contains material and consists of two activities. Third, assessments from material and media experts each with an average percentage of 89.3% and 89.5%. The results of assessments by students and experts show practicality and effectiveness with scores of 94% and 93% respectively, indicating usefulness and feasibility.